Improved outcomes and reduced costs associated with a health‐system–wide patient blood management program: a retrospective observational study in four major adult tertiary‐care hospitals. Issue 6 (2nd February 2017) - Leahy, Michael F.; Hofmann, Axel; Towler, Simon; Trentino, Kevin M.; Burrows, Sally A.; Swain, Stuart G.; Hamdorf, Jeffrey; Gallagher, Trudi; Koay, Audrey; Geelhoed, Gary C.; Farmer, Shannon L.
Abstract : BACKGROUND: Patient blood management (PBM) programs are associated with improved patient outcomes, reduced transfusions and costs. In 2008, the Western Australia Department of Health initiated a comprehensive health‐system–wide PBM program. This study assesses program outcomes. STUDY DESIGN AND METHODS: This was a retrospective study of 605, 046 patients admitted to four major adult tertiary‐care hospitals between July 2008 and June 2014. Outcome measures were red blood cell (RBC), fresh‐frozen plasma (FFP), and platelet units transfused; single‐unit RBC transfusions; pretransfusion hemoglobin levels; elective surgery patients anemic at admission; product and activity‐based costs of transfusion; in‐hospital mortality; length of stay; 28‐day all‐cause emergency readmissions; and hospital‐acquired complications. RESULTS: Comparing final year with baseline, units of RBCs, FFP, and platelets transfused per admission decreased 41% (p < 0.001), representing a saving of AU18, 507, 092 (US18, 078, 258) and between AU80 million and AU100 million (US78 million and US97 million) estimated activity‐based savings. Mean pretransfusion hemoglobin levels decreased 7.9 g/dL to 7.3 g/dL (p < 0.001), and anemic elective surgery admissions decreased 20.8% to 14.4% (p = 0.001). Single‐unit RBC transfusions increased from 33.3% to 63.7% (p < 0.001). There were risk‐adjusted reductions in hospital mortality (odds ratio [OR], 0.72; 95% confidence interval [CI], 0.67‐0.77; p < 0.001), length of stay (incidence rate ratio, 0.85; 95% CI, 0.84‐0.87; p < 0.001), hospital‐acquired infections (OR, 0.79; 95% CI, 0.73‐0.86; p < 0.001), and acute myocardial infarction‐stroke (OR, 0.69; 95% CI, 0.58‐0.82; p < 0.001). All‐cause emergency readmissions increased (OR, 1.06; 95% CI, 1.02‐1.10; p = 0.001). CONCLUSION: Implementation of a unique, jurisdiction‐wide PBM program was associated with improved patient outcomes, reduced blood product utilization, and product‐related cost savings.